Legal Discourse on Legalizing Cryptocurrency as Legal Tender in Indonesia: Insights from Global Practices - Christmas, Sandy Kurnia; Angelique, Aurellia (Journal of Judicial Review, 2024)
Cryptocurrency in Indonesia presents both advantages and challenges. The Indonesian government has not yet given legality to cryptocurrency as legal tender. However, even though it does not have specific regulations, this matter regarding crypto is described as a crypto asset in several legal regulations in Indonesia. This study aims to examine the potential for implementing cryptocurrency as legal tender in Indonesia and whether it can be regulated within the country's legal framework. It also compares Indonesia's situation with the legal systems of El Salvador and the Central African Republic, where cryptocurrency has been adopted as legal tender. This study was studied in a socio-legal research method review, which used several approaches from a legislative perspective, case studies, and a comparison of state laws.  The findings reveal that while there is no specific law in Indonesia that regulates cryptocurrency as legal tender, there are existing regulations governing crypto assets, overseen by the country's futures supervisory agency. Crypto in Indonesia does not yet meet the standard requirements as legal tender, such as tability of value, divisibility, and uniformity. Based on a comparison of laws in El Salvador and the Central African Republic that have established crypto as legal tender, several comparisons can be seen starting from the structure, substance, and legal culture, where support for regulations and institutions as well as community support can maximize the legalization of crypto in Indonesia, but this requires several special considerations related to the impact and influence that will be faced if the legality of crypto is implemented. Therefore, based on the comparison of the law, it will be seen whether Indonesia.